A high resolution analysis of weak absorption band of C2H2D2-trans: The v8+ v10 (Au) band; The XVIIIth Symposium and School on High Resolution Molecular Spectroscopy, June 30 - July 4, 2015, Tomsk, Russia - Litvinovskaya A. G. Anastasiya Georgievna (2015, 2015)
Title screen